Vaginal hysterectomy in non-prolapsed uterus: an old "new" option - Sotero, Gonzalo (2015)
OBJETIVE: To analyze the results of vaginal hysterectomies performed without uterine prolapse. DESIGN: Descriptive study. LUGAR: Hospital Center "Pereira Rossell" of Montevideo, Uruguay. MATERIALS AND METHODS: We reviewed the medical histories of vaginal hysterectomies performed since 1997. operative time, length of stay, complications were examined and compared to the reference series. RESULTS: 200 vaginal hysterectomies was performed without major complications. CONCLUSIONS: In those patients requiring hysterectomy for benign cervical cancer and pathology to the stage IA1, the route of choice is vaginal.